2020
DOI: 10.5539/jas.v13n1p165
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Maize Yields from In-Season GreenSeeker Normalized Difference Vegetation Index and Dry Biomass as Influenced by Different Nutrient Combinations

Abstract: To mitigate low maize productivity, improve on-farm planning and policy implementation, the right fertilizer combinations and yield forecasting should be prioritized. Therefore, this research aimed at assessing the effect of applying different nutrient combinations on maize growth and yield and in-season grain yield prediction from biomass and normalized difference vegetation index (NDVI) readings. The research was done in Embu and Kirinyaga counties, in Central Kenya. Nutrient combinations tested were P+K, N+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The study stated that the application of balanced amount of fertilisers can be observed from NDVI reading. This can help in keeping track of and monitoring the nutrient supply (Otieno et al, 2020).…”
Section: Yield Monitoring Forecasting and Harvestingmentioning
confidence: 99%
“…The study stated that the application of balanced amount of fertilisers can be observed from NDVI reading. This can help in keeping track of and monitoring the nutrient supply (Otieno et al, 2020).…”
Section: Yield Monitoring Forecasting and Harvestingmentioning
confidence: 99%